Analisis Evaluasi Kebijakan dan Pengembangan Kurikulum di SDIT Insantama Leuwiliang - Rusdiono Mukri; Sofyan Sauri (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2023)
This study aims to analyze policy evaluation and curriculum development in Islamic educational institutions, especially at SDIT Insantama Leuwiliang, Bogor Regency. This research uses descriptive qualitative method which is carried out by collecting data obtained from documentation, observation and interviews. The results show that through policies and curriculum development that are evaluated periodically, SDIT Insantama Leuwiliang which was founded in 2011 is able to educate students to have an Islamic personality, have an Islamic knowledge, and understand their duties as representatives of Allah (Khalifatullah) on earth through talents, skills and expertise. The results also show that the vision and mission of SDIT Insantama Leuwiliang are in accordance with the vision and mission of Islamic educational institutions that are attached to the long-term ideals and goals of Islamic values, namely realizing mercy for all mankind. Keywords: Evaluation; Policy; Curriculum